View of Santa Clara Valley from the west near Los Gatos - Gordon, John C., 1887-1967 (photographer) :::Creator::::::::::::
Panoramic landscape of orchards, water towers, houses, and outbuildings spread across the Santa Clara Valley, probably near Los Gatos. The outline of a city center can be seen near the horizon, in the center right of the panorama, this is probably downtown San Jose. At the bottom left of the panorama, a series of outbuildings or agricultural facilities can be seen. To the far right, two relatively large houses sit at the foot of several hills. To the far left, a series of relatively smaller houses and outbuildings are loosely grouped into a small neighborhood. Slightly Northeast of this neighborhood is very large house with the countours of a barn.